Internet infrastructure and competition in digital markets - Philip Hanspach (International Telecommunications Society (ITS), 2022)
Large digital platform companies increasingly integrate vertically by building Internet infrastructure, such as edge computing facilities, content delivery networks, or submarine cables. These investments enable new services while changing their bargaining power towards the upstream supplier. I model competing investment incentives in Internet infrastructure for an upstream player (e.g., an Internet Service Provider) and a large downstream platform and its effects on competition with smaller downstream platforms without proprietary infrastructure. Investment incentives increase discontinuously both upstream and downstream when the downstream platform has the larger network. With symmetric investment costs, the downstream platform will invest more than a pure upstream player. I discuss the model implications for net neutrality, network access regulation, and efficient side payments between platform and upstream industry.
Keywords: L13; L42; L51; L63; L86; 330; platforms; multi-sided markets; competition policy; net neutrality; Internet; telecommunications infrastructure